2021
DOI: 10.47059/alinteri/v36i1/ajas21046
|View full text |Cite
|
Sign up to set email alerts
|

Condition Index, Meat Yield and Biochemical Composition of Mediterranean Mussel (Mytilus Galloprovincialis Lamarck, 1819) from Canakkale Strait, Turkey

Abstract: The present study was performed in Çanakkale Strait from September 2012 to August 2013. Biochemical composition (protein, total lipid, moisture, and ash), condition index, and meat yield of Mediterranean mussel, Mytilus galloprovincialis in the net systems hung out the open sea cage units monthly. The mean condition index and meat yield of M. galloprovincialis were found 8.12±0.48 and 16.07±0.70%, respectively. A positive correlation was found between condition index and protein, carbohydrate, and meat yield w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…In this study, Koru and Deveboynu stations were found to have lower MY and CI compared to Çınarcık and Kapaklı stations. Environmental parameters, size, and reproductive period are directly related to CI, MY, and SCI (Acarli et al, 2015;Vural et al, 2015;Acarlı et al, 2018;Kızılkaya et al, 2019;Biandolino et al, 2020;Yıldız et al, 2021). In this study, differences were found between stations (p<0.05).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In this study, Koru and Deveboynu stations were found to have lower MY and CI compared to Çınarcık and Kapaklı stations. Environmental parameters, size, and reproductive period are directly related to CI, MY, and SCI (Acarli et al, 2015;Vural et al, 2015;Acarlı et al, 2018;Kızılkaya et al, 2019;Biandolino et al, 2020;Yıldız et al, 2021). In this study, differences were found between stations (p<0.05).…”
Section: Discussionmentioning
confidence: 44%
“…In this study, the lowest MY was observed at Koru station (21.54±4.01%), and the highest at Çınarcık station (24.51±2.96%). Yıldız et al (2021) found that the MY and CI of M. galloprovincialis (83.69 mm in length) in the Çanakkale Strait was 17.79% and 9.33 in April, respectively. Lök et al (2011) was determined that MY and CI of M. galloprovincialis was 27.05% and 11.53 (51.22 mm in length) in the Sinop-Içliman (Black Sea), and 22.63% and 10.47 (62.56 mm in length) in Edincikaltı (Marmara), 18.26% and 9.93 (50.44 mm in length) in Mersin Bay (Aegean Sea), respectively.…”
Section: Discussionmentioning
confidence: 92%
“…It is also applied as a measure of the apparent health and commercial quality of bivalves [ 21 , 43 ]. The monitoring of CI to assess growth in oysters has been widely documented [ 44 , 45 ]. As a physiological index, CI is highly influenced by gonadal development and the age of the oyster.…”
Section: Discussionmentioning
confidence: 99%
“…The condition index (CI) is commonly used to assess the health and quality of bivalves [24][25][26], and was calculated according to the following equation: CI = Tissue dry weight/Shell dry weight × 100…”
Section: Morphology and Species Identificationmentioning
confidence: 99%